Effect of Sorghum Mulches on Emergence and Seedling Growth of Beggarticks, Goose Grass, and Sesame - Juliet Chengetai Murimwa; Joyful Tatenda Rugare; Stanford Mabasa; Ronald Mandumbu (International Journal of Agronomy)
Rotation of sorghum (Sorghum bicolor L. Moench) with sesame (Sesamum indicum L.) in drought prone areas of Zimbabwe has raised concerns on whether these two crops are compatible in the rotational system. This is because sorghum is known to exhibit strong allelopathic effects on both crop and weed species. A greenhouse experiment was conducted to assess the effect of soil incorporated sorghum residues on the emergence and seedling growth of sesame and weeds. The emergence and early seedling growth of sesame and the weed significantly p<0.05 increased with increases in the amount of soil incorporated sorghum residues. Incorporating 27.7 g of the ground sorghum herbage caused a stimulatory effect on the emergence and early seedling growth of the test species. Liquid chromatography-mass spectrometry revealed the presence of 6 probable allelochemicals in sorghum residues, namely, 4-methylaminobutyrate, C16 sphinganine, oleamide, tauroursdeoxycholic acid, pisatin, and anhalonidine. From this study, it can be concluded that dry sorghum residues do not have an inhibitory effect on sesame emergence and growth at mulch rates that retard emergence and growth of weeds.